Altered relationship between anandamide and glutamate in circulation after 30 min of arm cycling: A comparison of chronic pain subject with healthy controls - Stensson, Niclas; Grimby-Ekman, Anna (Molecular pain, 2019)
The insufficient knowledge of biochemical mechanisms behind the emergence and maintenance of chronic musculoskeletal pain conditions constrains the development of diagnostic and therapeutic tools for clinical use. However, physical activity and exercise may improve pain severity and physical function during chronic pain conditions. Nevertheless, the biochemical consequences of physical activity and exercise in chronic pain need to be elucidated to increase the precision of this therapeutic tool in chronic pain treatment. The endocannabinoid system has been suggested to play an important role in exercise-induced reward and pain inhibition. Moreover, glutamatergic signalling has been suggested as an important factor for sensation and transmission of pain. In addition, a link has been established between the endocannabinoid system and glutamatergic pathways. This study examines the effect of dynamic load arm cycling (30 min) on levels of lipid mediators related to the endocannabinoid system and glutamate in plasma of chronic pain subjects and pain-free controls. Pain assessments and plasma levels of arachidonoylethanolamide (anandamide), 2-aracidonoylglycerol, oleoylethanolamide, palmitoylethanolamide, stearoylethanolamide and glutamate from 21 subjects with chronic neck pain (chronic pain group) and 11 healthy controls were analysed pre and post intervention of dynamic load arm cycling. Pain intensity was significantly different between groups pre and post exercise. Post exercise, anandamide levels were significantly decreased in health controls but not in the chronic pain group. A strong positive correlation existed between anandamide and glutamate in the control group post exercise but not in the chronic pain group. Moreover, the glutamate/anandamide ratio increased significantly in the control group and differed significantly with the chronic pain group post exercise. The altered relationship between anandamide and glutamate after the intervention in the chronic pain group might reflect alterations in the endocannabinoid-glutamate mechanistic links in the chronic pain group compared to the pain-free control group.